Bella Abzug for President campaign sign - Sahl, Ted (photographer):::Creator::::::::::::
Lesbian activists Rosalie Nichols, Johnie Staggs and Pat McAtee hold a sign with the words: "Bella for President, 1980," during Bella Abzug's presentation at San Jose State University in 1979.